2021
DOI: 10.1002/jeq2.20285
|View full text |Cite
|
Sign up to set email alerts
|

Applying the nutrient transfer continuum framework to phosphorus and nitrogen losses from livestock farmyards to watercourses

Abstract: Farmyards are commonly conceptualized as point sources of nutrient pollution nested within the wider agricultural landscape. However, within farmyards there are individual sources and delivery pathways, each of which is affected by a range of management practices and infrastructure. Rainfall mobilizes these nutrients, which may then be delivered to a receptor or to the wider drainage network. As such, the nutrient transfer continuum (NTC), which has been established as a framework to understand and mitigate nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In Beef Farm 1, L1 had the highest mean P concentrations than the other sampling locations because the sampling location was about 5 m from the beef farmyard which cows frequently visit. This frequency of animals using the same roadway increase the excreta deposited into the roadways thus, showing higher P relative to other farm roadways sections (Vero and Doody, 2021). Similar observations have been reported by McCormick et al (2009) who indicated that areas closer to farm yards had larger P concentrations due to their proximity to farm buildings thus, prone to receiving leakages from silos and yard washings.…”
Section: Spatial and Temporal Aspects Of Available P Concentrationssupporting
confidence: 81%
See 1 more Smart Citation
“…In Beef Farm 1, L1 had the highest mean P concentrations than the other sampling locations because the sampling location was about 5 m from the beef farmyard which cows frequently visit. This frequency of animals using the same roadway increase the excreta deposited into the roadways thus, showing higher P relative to other farm roadways sections (Vero and Doody, 2021). Similar observations have been reported by McCormick et al (2009) who indicated that areas closer to farm yards had larger P concentrations due to their proximity to farm buildings thus, prone to receiving leakages from silos and yard washings.…”
Section: Spatial and Temporal Aspects Of Available P Concentrationssupporting
confidence: 81%
“…Spatial results concur with animal movement dynamics, with some areas within the roadway network more vulnerable to P deposition and storage of nutrients within surface materials (i.e., as animals slow or are impeded) (Vero and Doody, 2021). It must also be noted that the present study only samples roadway materials, where fresh deposits on roadways would also contribute to roadway runoff concentrations during runoff events.…”
Section: Spatial and Temporal Aspects Of Available P Concentrationssupporting
confidence: 77%
“…A delivery point or area is where runoff enters waters. This approach has been applied at sub-catchment scale to nutrient losses and impact from farmyards (Vero and Doody, 2021) and drainage ditch networks to waters (Moloney et al, 2020).…”
Section: Ntc Frameworkmentioning
confidence: 99%
“…Recently, a nutrient transfer continuum (NTC) framework was applied to farmyards by Vero and Doody (2021). Only when information and knowledge on nutrient sources, mobilisation, delivery and impact are gathered, can the correct mitigation options for farmyard N and P losses be identified (Vero and Doody, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation